Lipidomics biomarkers in women with polycystic ovary syndrome (PCOS) using ultra-high performance liquid chromatography–quadrupole time of flight electrospray in a positive ionization mode mass spectrometry. (18th August 2019) - Vonica, Camelia Larisa; Ilie, Ioana Rada; Socaciu, Carmen; Moraru, Corina; Georgescu, Bogdan; Farcaş, Anca; Roman, Gabriela; Mureşan, Andrada Alina; Georgescu, Carmen Emanuela
Abstract: Polycystic ovary syndrome (PCOS), characterized by oligo-anovulation and androgen excess is considered a high-risk condition for metabolic disorders. Herein, untargeted metabolomics analysis was applied to women with PCOS, aiming to provide deeper insights into lipidomics biomarkers signature of PCOS, for better diagnosis and management. This was a cross-sectional study in which 15 Caucasian women with PCOS and 15 Caucasian healthy, age-matched women were enrolled. Lipidomics analysis was performed using Ultra-High Performance Liquid Chromatography–Quadrupole Time of Flight Electrospray Mass Spectrometry. Partial Least Squares Discriminant Analysis retrieved the most important discriminative metabolites. Significantly increased levels of triacylglycerol (18:2/18:2/0-18:0) in addition to cholestane-3beta, 5alpha, 6beta-triol (18:0/0:0) and cholestane-5alpha (18:1/0:0) appeared as valuable variables to differentiate subjects with PCOS from controls. Acyl-carnitine 2-hydroxylauroylcarnitine was significantly elevated in PCOS in opposition to decreased phosphocholines metabolites (18:1/18:4, 18:3/18:2), to suggest a metabolic pattern linked to lipid peroxidation. A high fat intake or reduced fat energy consumption during nighttime due to diminished ability to switch to lipid oxidation during fasting time possibly contribute to hypertriglyceridemia found in PCOS. Furthermore, inflammatory mediators including metabolites of the prostaglandin (PG) E2 pathway and oxo-leukotrienes (LT) were increased in patients with PCOS. Potential lipidomics biomarkers were identified that could stratify between women with PCOS and healthy controls. The results show particular alterations in acylglycerols, PGs and LTs and phosphocholines and carnitine metabolites. The lipidomics profiles of PCOS indicate a higher risk of developing metabolic diseases.